One Nation : What We Can All Do to Save America's Future - Carson, Ben; Carson, Candy (New York : Sentinel, 2014)
"Dr. Ben Carson made headlines with his keynote at the National Prayer Breakfast in February 2013. Standing just a few feet from President Obama, the neurosurgeon offered a common sense critique of liberal government, calling for a return to our historic culture of personal responsibility, free markets, and upward mobility. Now, in this sequel to their #1 New York Times bestseller America the Beautiful, Dr. and Mrs. Carson offer a bold plan to stop the country's slide into fiscal and moral decay. Avoiding the political correctness of politicians and the animosity of Washington lawyers, Dr. Carson calls for respectful discussion and disagreement, with no subjects off limits. Applying the problem-solving skills he honed as a surgeon, he takes on tough issues such as education, health care, family values, race relations, taxes, charity, and the role of faith in public life. In his journey from poverty to the top of his field, Dr. Carson has lived the American dream. He shows how we can save that dream for our future generations, by restoring a moral, informed citizenry that will support "one nation, under God, indivisible.""--
Keywords: Social values -- United States; POLITICAL SCIENCE / Government / National; United States -- Moral conditions; United States -- Politics and government -- 21st century